Dynamic Evolution of Antimicrobial Peptides Underscores Trade-Offs Between Immunity and Ecological Fitness - Hanson, Mark A.; Lemaitre, Bruno; Unckless, Robert L. (Frontiers in Immunology, 2019)
There is a developing interest in how immune genes may function in other physiological roles, and how traditionally non-immune peptides may, in fact, be active in immune contexts. In the absence of infection, the induction of the immune response is costly, and there are well-characterized trade-offs between immune defense and fitness. The agents behind these fitness costs are less understood. Here we implicate antimicrobial peptides (AMPs) as particularly costly effectors of immunity using an evolutionary framework. We describe the independent loss of AMPs in multiple lineages of Diptera (true flies), tying these observations back to life history. We then focus on the intriguing case of the glycine-rich AMP, Diptericin, and find several instances of loss, pseudogenization and segregating null alleles. We suggest that Diptericin may be a particularly toxic component of the Dipteran immune response lost in flies either with reduced pathogen pressure or other environmental factors. As Diptericins have recently been described to have neurological roles, these findings parallel a developing interest in AMPs as potentially harmful neuropeptides, and AMPs in other roles beyond immunity.